Study on muscle fatigue of rifle shooters using surface electromyogram - Tan, Janice Shih Jia. (2011)
Successful shooting has often been closely associated with accuracy and minimum transient movement in the body. Postural stability has been singled out as one of the most important determinants of successful rifle shooting. The basic demand of a rifle shooter is prolonged standing with maintenance of posture and studies have demonstrated electrical signs of fatigue in muscles on prolonged standing and its potential effects on postural control. The aims of the present study were: to investigate the electrical activities of the muscles on the lower limbs of rifle shooters in a typical shooting game; and to investigate the correlation between postural sway parameters and the electrical activities of the various muscles groups of the lower limbs.